1992
DOI: 10.1083/jcb.119.4.1003
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts express high levels of pp60c-src in association with intracellular membranes.

Abstract: Deletion of the c-src gene in transgenic mice by homologous recombination leads to osteopetrosis, a skeletal defect characterized by markedly deficient bone resorption (Soriano, P., C. Montgomery, R. Geske, and A. Bradley. 1991. Cell. 64:693-702), demonstrating a critical functional role of pp60c-src in osteoclast activity. Since decreased bone resorption could result from a defect either within the osteoclast or within other cells present in its environment, indirectly affecting osteoclast functions, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(142 citation statements)
references
References 52 publications
6
135
0
1
Order By: Relevance
“…1) (21). Cathepsin K (22, 23) and c-Src (24,25), which are known markers of osteoclasts, were also induced in the multinuclear cells. These results showed that the multinuclear TRAP-positive cells from RAW264.7 cells possessed major characteristics of osteoclasts.…”
Section: Resultsmentioning
confidence: 98%
“…1) (21). Cathepsin K (22, 23) and c-Src (24,25), which are known markers of osteoclasts, were also induced in the multinuclear cells. These results showed that the multinuclear TRAP-positive cells from RAW264.7 cells possessed major characteristics of osteoclasts.…”
Section: Resultsmentioning
confidence: 98%
“…It has been shown that pp60 ....... is required for the ruffled border formation of osteoclasts [16][17][18][19]. Since it is suggested that PI-3 kinase is activated by pp60 ....... [20,21], it is natural to speculate that PI-3 kinase is involved in osteoclastic bone resorption.…”
Section: Resultsmentioning
confidence: 99%
“…Fax: (81) (3) 3812-0544. in mice induced osteopetrosis, a disease characterized by reduced osteoclastic bone resorption [16]. Indeed, osteoclasts have been reported to express a high level of pp60 ..... [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although Src is expressed in most cell-types, targeted disruption of Src leads to only one major phenotype ± osteopetrosis or a failure to resorb bone due to an intrinsic defect in osteoclasts Soriano et al, 1991). Osteoclasts express high levels of Src and the lack of this molecule leads to dramatic defects in the ability of this cell-type to resorb bone and organize its actin cytoskeleton (Horne et al, 1992;Lowell et al, 1996;Ne et al, 1996;Schwartzberg et al, 1997). However, the nature of the defect(s) in signal transduction in these cells remains unclear.…”
Section: Function Of the Src Domains In Intracellular Signalingmentioning
confidence: 99%